Effects of COVID-19 Pandemic on the Mental Health of Women and Treatment of Mental Disorders in the Unani System of Medicine: An Overview - Ateeque Ahmed, Sana K.; Sidra; Sheema; Jahan, Nasreen; Ansari, Abid Ali (Current Traditional Medicine, 2024)
Background: The world miserably collapsed when the COVID-19 (Coronavirus disease) pandemic was going out of control. The ongoing crisis has damaging effects on the mental health of individuals, predominantly women, in both developed and developing countries. Women in developing countries, both as frontline workers and at home, are at increased risk of mental health problems (specifically mental disorders). A few observational studies related to the COVID- 19 pandemic have reported a higher prevalence of mental health problems like stress, anxiety, depression, insomnia, fear, delirium, hysteria etc. among women compared to men. Thus, understanding the effects of the COVID-19 pandemic on women's mental health are as important to discuss as their physical health effects. Objective: The Unani System of Medicine (USM) has a holistic approach to preventing, treating, and curing mental disorders. The present article aimed to provide an overview of the effects of the COVID-19 pandemic on women's mental health and its containment measures described in classical Unani texts besides their relevance in the current outbreak. Materials and Methods: A manual literature survey of classical Unani literature such as Firdaus- al-hikmat, Al Qanoon-fit-tib, Zakheera Khwarzam Shahi, and Kamilus Sana was conducted to collect the information available on the strategic approaches of health promotion and disease prevention in Unani Medicine. To obtain the appropriate English equivalent words for Unani terms and the scientific name of the drugs, “Standard Unani Medical Terminology” and “Classification of Unani Drugs” were consulted, respectively. Many pharmacological books and papers were considered from PubMed, Google Scholar etc. Results: According to the literature review results, Unani doctors have pushed the adoption of personalised and predictive methods for preserving health and preventing diseases. The main focus is to treat the fragile population, i.e., women affected by mental illnesses. Conclusion: The present article emphasizes the mental health problems among women provoked by the COVID-19 pandemic, their possible etiopathogenesis, prevention, and psychological, regimental and pharmacological management of the USM.
Keywords: Unani system of medicine